HOTS-Based Learning Supplementary Book for Teaching English at First Semester of Seventh Grade Students - Widyastuti, Ni Wayan Suwardewi; Nitiasih, Putu Kerti; Budiarta, Luh Gd Rahayu (Universitas Pendidikan Ganesha, 2023)
The teachers had not implemented HOTS-based learning well, moreover there were no varied introductory books let alone additional sources that support the learning process in the 21st century. This is very important to note considering that children have entered junior high school and have stepped on a higher level of learning. This study aims to developing a HOTS-based supplementary learning book for 7th graders in the first semester. This research design used the ADDE (Analysis, Design, Development, and Evaluation) model, in which the object of the research was a HOTS-based English learning book. The development of the book was based on the English learning syllabus used. Observations, interviews, document studies, and expert judgments were used to collect data in this study. A teacher in in junior high school was a participant in this study. The study found that this supplementary material book gave satisfaction to the target user. In addition, judging from the qualifications of experts, this product was referred to as a very good worksheet so that it was expected to be useful for 7th grade students and teachers.